Factors of innovation creation within functional heterogeneous project teams Case study: ABB Group - Berdysheva, Ekaterina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The research topic of the work is: “Factors of innovation creation within functionally heterogeneous project teams”. The research question is “What are the factors of innovation creation within functionally heterogeneous project teams?” The subject of this research is to explore the teams of projects, aimed at creating innovations, and understand how innovation is generated through project team work within them in term of factors. In line with the purposes of this study, firstly, it was analyzed what factors of such teams’ work are affecting creating innovation positively and negatively on the base of chosen literature and a preliminary conceptional framework was formulated, and secondly, the research of the work of project teams in one of the divisions of ABB company has been done and other factors and interdependencies between them have been added to the conceptional framework. This final conceptional framework constitutes the essense of the work findings and can be used as a tool to analyze the innovation creation process in functionally heterogeneous project teams